The influence of mountain catchment area control measures on land management in the groot-Winterhoek area of the Western-Cape : ecological, economic and social implications - Bands, Donald Patrick (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Bosbou) -- University of Stellenbosch, 1985.